Proceso de enseñanza aprendizaje en la Matemática con los estudiantes del Tercer Año de la Unidad Educativa “Atanasio Viteri Karolys. - Trávez Chiluisa, Carmen Elizabeth (2022)
The goal of this study was to identify the issues that arise in the teaching and learning of mathematics. The study emerged from a widespread worry about the present situation of the students in the third year of the Educational Unit "Atanasio Viteri Karolys," because many of them display deficiencies in solving mathematical problems, leading us to believe they have a low level of arithmetic ability. As a result of this, and as a response to the situation, The major goal of this written work is to provide a handbook of ludic activities for solving third-year mathematical problems in order to achieve considerable learning in Mathematics, with paradigm shifts, new leisure activities, and a favorable learning environment. To achieve the goal, factual information must be gathered using qualitative-quantitative methodology, as it is investigated from the characteristics or relevant aspects of those involved, using both deductive and inductive methods, which allow for the presentation of concepts, principles, rules, definitions, and operations, which are then analyzed, synthesized, compared, generalized, and demonstrated in relation to the teaching-learning process of students. Following the implementation of the suggestion, a favorable range of positive results was attained. The PEA of Mathematics improved as a consequence of the entertaining activities, which piqued the pupils' interest and enthusiasm to study.